Back Cover: Resistive Switching Nanodevices Based on Metal–Organic Frameworks (ChemNanoMat 1/2016). Issue 1 (23rd December 2015) - Wang, Zhengbang; Nminibapiel, David; Shrestha, Pragya; Liu, Jianxi; Guo, Wei; Weidler, Peter G.; Baumgart, Helmut; Wöll, Christof; Redel, Engelbert
Abstract : Bipolar switching was demonstrated in crystalline and monolithic SURMOF (surface‐anchored metal–organic framework) thin films shown on the Back Cover. By using conductive substrates as bottom and top electrodes, these metal‐organic‐hybrid materials act as novel nonvolatile RRAM memory devices. The huge flexibility of the SURMOF‐RRAM device was further enhanced by loading ferrocene into the free pores of the framework. This result demonstrates a huge potential of SURMOF thin films as scalable active materials for the next‐generation of digital processing and organic‐based microelectronic devices. More information can be found in the Full Paper by H. Baumgart, C. Wöll, E. Redel, et al. onpage 67 in Issue 1, 2016 (DOI:10.1002/cnma.201500143 ).